Studies on the Formation and Inactivation of Human Blood Coagulation Product I - Spaet, Theodore H.; Cintron, Jose (Thrombosis and Haemostasis, 1961)
Although thrombin formed in product I generating mixtures, product I and thrombin activity were essentially uncorrelated. The addition of thrombin to generating mixtures caused acceleration of product I formation, but failed to elicit product I formation in “incomplete” systems. Product I was found to be relatively stable when formed with diluted reagents or separated from certain plasma proteins. When inactivation occurred with concentrated reagents, activity was restored only with further addition of reagents containing AHF. The stability of product I at 57° C is similar to that of AHF. When product I is reacted with a source of phosphatide to form blood thromboplastin, little product I “consumption” occurs.